2021
DOI: 10.1038/s41598-020-80335-9
|View full text |Cite
|
Sign up to set email alerts
|

Particle size-related limitations of persistent phosphors based on the doped Y3Al2Ga3O12 system

Abstract: Co-doped Ce3+, Cr3+ and Pr3+ yttrium–aluminium–gallium garnet powders of various sizes were obtained by co-precipitation method. The microstructure and morphology were investigated by XRPD, TEM and gas porosimetry. The luminescence properties were studied by excitation and emission spectra, quantum yield and decay times. Thermoluminescence measurements were performed to evaluate the activation energy, traps redistribution and frequency factor. Limitation in the energy transfer between dopant ions in the small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 70 publications
4
21
0
Order By: Relevance
“…This is because the peak has not shifted as the initial population of trapped charges decreases. From the point of view of the activation energy, the first maximum in all samples is the same and is about 0.75 ± 0.02 eV, which is close to the value observed previously for the same matrix with different co-dopants [17,40]. In contrast, the activation energy of the second maximum noticeably decreased from about 0.9 to 0.5 eV with increasing an annealing temperature.…”
Section: Thermoluminescence Analysissupporting
confidence: 88%
See 3 more Smart Citations
“…This is because the peak has not shifted as the initial population of trapped charges decreases. From the point of view of the activation energy, the first maximum in all samples is the same and is about 0.75 ± 0.02 eV, which is close to the value observed previously for the same matrix with different co-dopants [17,40]. In contrast, the activation energy of the second maximum noticeably decreased from about 0.9 to 0.5 eV with increasing an annealing temperature.…”
Section: Thermoluminescence Analysissupporting
confidence: 88%
“…The signal was collected using PMT R13456 (Hamamatsu Photonics, Shizuoka, Japan Shizuoka, Japan) with a filter 721/65 Brighline HC (Semrock Inc., Rochester, NY, USA). Powder samples were prepared for measurements the same as was described in our previous work [17] For detailed analyses of the traps redistribution as an annealing temperature function, the T max -T stop (partial cleaning) experiment proposed by McKeever was performed [21]. The sample was irradiated at room temperature with the following partially heating to a temperature T stop and cooling back to room temperature (25 • C).…”
Section: Characterization Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, which it is also growing near to the NiO lattice, 2. The presence of dopants will affect the surface energy or the energy of grain boundaries through its interacts with surface/grain boundaries, which may lead to the creation of more surfaces/grain boundaries [25]. The earlier author, Oindrila Mondal et al, have also reported the influence on various dopants with different ionic radii in CaTiO 3 .…”
Section: Xrd Analysismentioning
confidence: 98%